Rubberwood; Swantimber production and recovery studies - Gan L T; Chew O K; Ho C Y (In: Proceedings of the 2nd Rubberwood Seminar, 19-20 November 1985, Forest Research Institute of Malaysia, Kuala Lumpur, Malaysia, pp.97-122., 1985)
This paper reports the logistics of on-site extraction of Heveawood sawntimber (that can be used for furniture manufacturing) with conventional portable band saws in four replanting areas. Log and sawntimber recoveries from nine 24 to 28 years of old Hevea cultivars comprising two seedling families and seven clonal buddings are also examined. The pros and cons of the system are identified and where necessary, alternatives to overcome shortcomings are proposed.
Keywords: Rubberwood